The Effect of Counseling to Improve Children's Mentality in Education - Annisa Arrumaisyah Daulay; Hesti Sasmitha; Anggun Sri Cahayati; Hendra Pratama Sihombing; Rean Ikhsanul (Universitas Muhammadiyah Enrekang, 2022)
In this study the authors took the title The influence of counseling to improve children’s mentality in education. This article aims to examine how big the role of the school environment and the influence of counseling in improving the mentality of students. Guidance and counseling are useful for helping students both individually and in groups regarding problems that arise. Faced in order to form independent students and can develop in a better direction. The influence on students with the guidance and counseling services, namely students can develop their potential, talents and interests as well as mentally according to what students want, so that students can improve their performance well academic and non-academic.